Anacroneuria (Plecoptera: Perlidae) from Caldera River, Chiriquí, Panamá, with new distribution records, and comments on altitudinal distribution and seasonal variation - Castillo Sánchez, Kayla; Aguirre, Yusseff; Ríos González, Tomás; BERNAL VEGA, Juan Antonio (Revista de Biología Tropical, 2018)
Plecoptera order is a basal group of aquatic insects, also known as stonefly. In order to contribute to the taxonomic and ecological knowledge of the genus Anacroneuria, nymphs were collected in the upper and low parts of the Caldera River, in the Chiriquí province. For this, field trips were carried out once a month, from January to December of 2015. A total of seven stations were sampled, and nymphs were collected on rocks and submerged leaf litter, manually with entomological tweezers, and with a triangular net; nymphs were later transported and reared in aquarium systems in the laboratory, and their growth was followed. A total of 485 nymphs were collected, with the emergence of 138 adults. Five species of Anacroneuria: Anacroneuria annulipalpis Klapálek, 1922, A. benedettoi Stark, 1998, A. planicollis Klapálek, 1923, A. quetzali Gutiérrez- Fonseca y Springer, 2015, A. marca Stark, 1998 and two unknown species were obtained after nymphs rearing. The distribution range of A. benedettoi was extended to the Chiriqui province. The first record for A. quetzali in Panamá is commented. In addition, data of altitudinal distribution, seasonal variability and environment requirements were mentioned. We recommend to expand studies on Plecoptera nymph associations with adult forms in other areas of Panama and the Neotropics, as well as to increase the knowledge about their biology and ecology.